TECHNICAL AND ECONOMIC OPTIMIZATION OF THE DAILY WORK OF THE ACCUMULATOR IN SOLAR-WIND POWER GENERATION SYSTEMS - V. V. Fedorenko; V. V. Samoylenko; V. S. Azab; I. V. Samoylenko (Современная наука и инновации, 2022)
The Use of solar and wind energy as an alternative source is an actual and promising direction of renewable energy sources.